Non-necrotizing colonic granuloma induced by schistosomiasis - Thein Swe; AAMA Baqui; Akari Thein Naing; Tajruba Baqui; Jagannath Sherigar; Mohamed Mansour (Greater Baltimore Medical Center, 2016)
Schistosomiasis is an important parasitic disease with various clinical presentations caused by trematode blood flukes. It can present with asymptomatic, chronic colonic ulcerations, strictures, or inflammatory mass causing bowel obstruction. Intestinal polyps are uncommon and induced by antigens released from the schistosome eggs that trigger a cell-mediated inflammatory response with granuloma formation involving T cells, macrophages, and necrosis. This is very relevant while evaluating chronic intermittent gastrointestinal symptoms and eosinophilia in an immigrant patient from endemic areas of schistosomiasis. Here, we describe a case of chronic intestinal schistosomiasis which was found to have schistosomiasis-induced colonic polyp with non-necrotizing granuloma. With increase in immigrant population from the endemic areas of schistosomiasis in the United States, physicians should be aware of this disease and its various manifestations. Gastroenterologist should keep this as one of the differentials for colonic polyps. Diagnosis and treatment in time prevents further progression of the disease and its complications.